SOCIAL INTELLIGENCE IN RELATION TO MENTAL HEALTH ON SECONDARY SCHOOL STUDENTS IN KERALA - Deepa Varghese (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of this study is to find out the relationship between the variables Social Intelligence and Mental Health is studied, with respect to the classificatory variables Gender, Locale and Type of Management. The investigator used Normative Survey Method for collection of data .The study is conducted on the population of secondary school students of Kerala. The present study conducted on 360 secondary school students of standard IX of Kerala district. The sample selected by stratified random sampling technique Social Intelligence Scale prepared by the investigator with the help of the supervisor. Mental Health Scale namely Warwick Edinburgh Mental WellbeingScale (WEMWBS), adopted by the investigator. The findings of the study revealed a positive correlation between the two variables in total samples and sub samples based on gender, locale and type of management. However, the difference in the correlation coefficients for each classificatory variable revealed a significant difference between social intelligence and mental health based on locale but not with respect togender or type of management.